Teaching Research Ethics: Can Web-Based Instruction Satisfy Appropriate Pedagogical Objectives? - Schrag, Brian (Science & Engineering Ethics, 2005)
Ethical tasks faced by researchers in science and engineering as they engage in research include recognition of moral problems in their practice, finding solutions to those moral problems, judging moral actions and engaging in preventive ethics. Given these issues, appropriate pedagogical objectives for research ethics education include (1) teaching researchers to recognize moral issues in their research, (2) teaching researchers to solve practical moral problems in their research from the perspective of the moral agent, (3) teaching researchers how to make moral judgments about actions, and (4) learning to engage in preventive ethics. If web-based research ethics education is intended to be adequate and sufficient for research ethics education, then it must meet those objectives. However there are reasons to be skeptical that it can.